International short term consultancy: final report to PROCIANDINO IICA BID. Leguminosas de grano - Slinkard, Alfred E. (IICA, 2020)
The document presents: 1) a general information; 2) specific objectives of the consultant: genetic improvement and agronomic improvement. Accordingly, the objective of this consultancy is to integrate the current information available on faba bean and lentil breeding and management into a recommended program of action so that IICA can better coordinate the program on improved production efficiency of faba bean and lentil in Colombia, Peru, Bolivia and Ecuador. 3) Work that was done, results, conclusions and recommendations: a) detailed description of work done, results and conclusions by country; b) recommendations to improve the effectiveness and efficiency of the grain legume project in the andean countries. Finally, 16 appendixes are included.